PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN DAN RETURN ON EQUITY TERHADAP NILAI PERUSAHAAN PROPERTY AND REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Reni Dahar; Nino Sri Purnama Yanti; Fitria Rahmi (Universitas Dharma Andalas, 2019)
This research is an empirical study conducted to prove the effect of capital structure, firm size and Return On Equity on firm value. This study is a proposed hypothesis testing related to the influence of the independent variables on the dependent variable. The population is the Property and Real Estate companies that are registered in Indonesian Foam Securities from 2012 to 2016, which amount to 10 companies. The technique used in sampling is the census method, where the entire population is sampled (Sarwono, 2012). The results of the research partially show that the proxied Capital Structure with DER has a significant effect on the value of the company proxied by PBV, the size of the company proxied by Logaritma natural (LN) total assets does not significantly affect the value of the firm proxied by PBV. The results of the simultaneous research show that the Capital Structure proxied by DER, the size of the company proxied by Logaritma natural (LN) total assets and ROE has a significant effect on the value of the company proxied by PBV on Property and Real Estate Companies Listed on the Indonesia Stock Exchange.